Business-led sustainable consumption initiatives: impacts and lessons learned. Issue 1 (13th February 2017) - Bocken, Nancy
Abstract : Purpose: To mitigate negative human-induced impact on the planet, consumption patterns need to be changed urgently. The purpose of this paper is to investigate how companies can drive sustainable consumption patterns. Design/methodology/approach: The paper discusses six illustrative cases of sustainable consumption initiatives by companies: their strategies, initiatives and impacts. Findings: A "business-led sustainable consumption strategies framework" was developed to analyse the cases. It was found that companies apply individual, social and wider contextual influencing tactics to encourage sustainable consumption. The case initiatives emerged without regulatory pushes. It was found that collaborative initiatives could be impactful, because multiple stakeholder influence helps normalise new behaviour. Regulation helps to level the playing field in an industry and potentially force absolute consumption reductions. Practical implications: This work provides insight into the potential of business-led sustainable consumption initiatives and the strategies to be used. Companies are making important steps to encourage sustainable consumption, but initiatives have not yet achieved the scale to significantly transform consumption patterns. Further business experimentation with social marketing type of techniques is recommended. Future work is required to map out the most suitable strategies to encourage sustainable consumption by industry. Originality/value: This paper has given new insight in the potential future role of companies in sustainable consumption. Businesses are positioned as the initiators of sustainable consumption patterns: their expertise can be used to stimulate and adopt sustainable consumption patterns with customers. This work sheds light on how businesses can use social marketing-type techniques and business model innovation to drive sustainable consumption. Finally, it contributes to the understanding of the scale and effectiveness of business-led sustainable consumption initiatives.